Lactiplantibacillus plantarum L47 and inulin affect colon and liver inflammation in piglets challenged by enterotoxigenic Escherichia coli through regulating gut microbiota - Miao, Jingna; Cui, Leihong; Zeng, Hui; Hou, Meixin; Wang, Jingxuan; Hang, Suqin (Frontiers in Veterinary Science, 2024)
IntroductionInfection by pathogenic bacteria during weaning is a common cause of diarrhea and intestinal inflammation in piglets. Supplementing the diet with synbiotics is beneficial for animal health. The strain of Lactiplantibacillus plantarum L47 (L47) isolated in our lab exhibited good probiotic properties when combined with inulin. Here, the effectiveness of combining L47 and inulin (CLN) in protecting against enterotoxigenic Escherichia coli (ETEC) induced colon and liver inflammation in weaned piglets was evaluated.MethodsTwenty-eight piglets aged 21 days were randomly assigned into 4 groups: CON (control), LI47 (oral CLN culture fluid, 1010 CFU/d of L47 and 1 g/d of inulin), ECON (oral ETEC culture fluid, 1010 CFU/d), and ELI47 (oral CLN and ETEC culture fluid). After 24 days, the colon and liver samples were collected for further analysis.Results and discussionCLN alleviated colon damage caused by ETEC challenge, as evidenced by an increase of colonic crypt depth, mRNA expression of tight junction Claudin-1 and Occludin, GPX activity, the concentration of IL-10 and sIgA (p < 0.05). Moreover, there was a decrease in MDA activity, the load of E. coli, the concentration of LPS, gene expression of TLR4, and the concentration of TNF-α and IL-6 (p < 0.05) in colonic mucosa. Additionally, CLN counteracted liver damage caused by ETEC challenge by modulating pathways associated with immunity and disease occurrence (p < 0.05).ConclusionSupplementing with CLN alleviated colon inflammation induced by ETEC challenge by decreasing the E. coli/LPS/TLR4 pathway and regulating hepatic immune response and disease-related pathways, suggesting that CLN could protect intestinal and liver health in animals.